DESIGN OF HYDRAULIC FRACTURING CARBONATE RESERVOIR USING A SIMULATOR IN THE IQ FIELD X WELL - Irmaya, Aisyah; Hidayat, Muh Iqbal Hidayat; Yunita, Lia Yunita (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
The inability of a reservoir to pass large amounts of fluid can be caused by very low permeability. Objective: This research aims to increase well productivity in wells that have low permeability. Based on reservoir data, the permeability in the IQ well is tight permeability, namely 0.153 mD, so that fluid in the reservoir cannot flow into the well due to the low permeability of the formation. The low permeability of the formation resulted in a low production rate of 39 BLPD. Methodology and results: in this research a stimulation acidizing method was used but this method was less than optimal (seen from the absence of a pressure drop after acid was injected at a high flow rate), so a hydraulic fracturing method was carried out on the IQ well to increase well productivity. The results of this research use the PKN (Perkins, Kern & Nordgren) fracturing model to obtain a fracture length greater than the fracture height. The fracturing fluid used as pad and slurry is YF120.HTD and the flush fracturing fluid used is 4% KCL Water. The proppant used is Carbolite 20/40. The resulting fracture geometry was 111 ft, fracture height 55 ft and fracture width 0.375 in. The conductivity value of the fracture formed was 18.1 mD with a fracture permeability of 320,177.383 mD/ft. The productivity index increased by 2,945 with a production rate of 440.14 BFPD. The total cash flow obtained was 4,858,624.11 and NVP 2,413,572.70. The capital issued will be returned within 21 days. Conclusion: based on the results above, the IQ well is suitable for hydraulic fracturing